Fenomenologi Literasi Kritis Mahasiswa Guru Sekolah Dasar pada Era Abad 21 - Octavian Muning Sayekti; Haryanto; St. Kartono (Jurnal Pendidikan dan Pengajaran, 2022)
Critical literacy skills still need to be developed, considering that the essential power of students is not yet maximized, which is characterized by being easily provoked and having difficulty solving problems. Candidates for elementary school teachers who will later be in control at the basic education level are expected to master these abilities before they teach them to students. This study aims to analyze the extent of critical literacy mastery of elementary school teacher education students. The method used is qualitative with a phenomenological approach. The research was conducted at the Department of Elementary School Teacher Education, with 142 students. To collect data, this study used interviews, observation, and documentation. The data analysis technique uses the Bogdan and Biklen model, namely analyzing data by narrowing the findings based on phenomena. The result of this research is that the mastery of critical literacy, owned by the Elementary School Teacher Education Study Program students, is quite good even though all students do not evenly share this mastery. Mastery of critical literacy is manifested in collaborative activities, socio-cultural linkages, and the involvement of reflective thinking. This study implies that essential literacy learning should be part of the curriculum to have an honest and targeted impact.